The influence of commuting time on students’ academic performance and its internal mechanism: an empirical analysis based on CEPS data - Shan, Ke (Frontiers in Psychology, 2026)
BackgroundThis study examines the relationship between commuting time and students’ academic performance, further explores the impact of commuting time on academic performance and its underlying mechanisms, and analyzes strategies to mitigate the negative effects of commuting time on student academic performance.MethodsThe data source for this study is the 2014–2015 China Education Panel Survey (CEPS). This study first employs linear regression to analyze the impact of commuting time on students’ academic performance (Chinese, mathematics, and English scores). It then utilizes the PROCESS procedure to examine the mediating effects of psychological fatigue and learning engagement between commuting time and academic performance. Finally, an interaction term between commuting time and commuting mode is constructed, and hierarchical regression is applied to test the moderating effect of commuting mode on the relationship between commuting time and students’ academic performance.Results(1) According to linear regression findings, each additional minute of commuting time correlates with a 0.04-point decrease in Chinese scores, a 0.032-point decline in math scores, and a 0.05-point drop in English scores. (2) The negative impact of commuting time on students’ academic performance exhibits significant variation based on individual student and family factors. (3) Learning engagement and psychological fatigue partially mediate the relationship between commuting time and student performance. (4) Commuting mode significantly moderates the impact of commuting time on students’ academic performance.ConclusionCommuting time significantly impedes students’ academic performance. Learning engagement and psychological fatigue partially mediate the relationship between commuting time and students’ academic performance in this population. Commuting mode significantly moderates the effect of commuting time on students’ academic performance. Compared to passive commuting modes, active commuting intensifies the negative impact of commuting time on academic performance. To mitigate the negative effects of commuting time on students’ academic performance, school administrators should optimize campus locations, implement proximity-based enrollment policies, enhance boarding services, and provide psychological counseling and academic support to students.